Studies of the Logistics Services Market: Information and Analytical Support and a System of Statistical Indicators - N. HRYNCHAK (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
Information and analytical database for the market support is required to prevent communications of contradictory information to higher levels of management, with adverse effects for the process of taking rational management decisions. The article’s objective is to substantiate the information and analytical support for studies of the logistics services market, with constructing a system of statistical indicators for this market assessment, to be laid as the solid basis for elaborating medium-term and long-term strategies and policies of the logistics services market in Ukraine. A definition of information and analytical support for studies of the logistics services market is given; a review of secondary sources of data for this market studies is made. A conceptual model for information and analytical studies of the logistics services market is proposed. The key statistical indicators for studies of this market are identified, with substantiating the feasibility of their use in computing multivariate indicators for the assessment of performance and capacities of the logistics services market in Ukraine. The core criteria to be met by the abovementioned system of statistical indicators are highlighted. A system of statistical indicators for the assessment of the logistics services market is proposed, containing four modules. It allows for diagnosis of this market performance and tendencies, with accounting for the impact of other related markets and activities, and for forecasting. This system, constructed with consideration to the global practice, is designed for comprehensive studies of the logistics services market.